Cutting-Edge Policies and Services for Addressing Campus Sexual Violence - Merle Weiner (Academic Chairpersons Conference Proceedings, 2018)
The #MeToo movement and the Trump administration’s changes to Title IX guidance have raised new issues, questions, and demands regarding how colleges and universities should be addressing sexual and gender-based violence on their campuses. Within this milieu, it is worth considering some of the new policies and services that can improve a campus’s response to sexual and gender-based violence. In particular, this session will explore emerging best practices, including alternatives to universal mandatory reporting as well as programs that provide legal services to student survivors. Time permitting, this session will also touch upon such hot topics as the burden of proof in disciplinary proceedings and the desirability of restorative justice. Lecture, discussion, and exercises will be used to inform participants of the need for certain new policies and services, their legality, and ways in which participants might advance these new practices on their own campuses.
Keywords: Policies Services Sexual Violence Campus Title IX